Executive Compensation, Institutional Ownership, and Financial Performance (A Study on Manufacturing Companies in Indonesia) - Anwar Ibrahim, Zaky; Atmaji, Atmaji (Journal of World Science, 2023)
This research aims to determine and analyze Executive Compensation, Ownership and Financial Performance of Manufacturing Companies in Indonesia. The method used in this research is quantitative. The population of this research is all companies operating in the manufacturing sector registered on the BEI in 2019 - 2022. The sample in this study was selected using a purposive sampling method. The research results show that executive compensation significantly impacts manufacturing company performance through ROA but is less significant about ROE. Nonetheless, well-compensated executives are motivated to increase profits, potentially reducing agency costs. However, factors such as initial solid performance and external events such as COVID-19 may influence the impact of executive compensation on performance. In addition, institutional ownership does not significantly influence company performance because institutional investors tend to prioritize their portfolios and remain passive towards managerial activities, thereby rejecting the hypothesis that supports a significant positive effect of institutional ownership on performance.